Do oral bacteria alter the regenerative potential of stem cells? A concise review. Issue 9 (8th June 2015) - Chatzivasileiou, Kyriaki; Kriebel, Katja; Steinhoff, Gustav; Kreikemeyer, Bernd; Lang, Hermann
Abstract: Mesenchymal stem cells (MSCs) are widely recognized as critical players in tissue regeneration. New insights into stem cell biology provide evidence that MSCs may also contribute to host defence and inflammation. In case of tissue injury or inflammatory diseases, e.g . periodontitis, stem cells are mobilized towards the site of damage, thus coming in close proximity to bacteria and bacterial components. Specifically, in the oral cavity, complex ecosystems of commensal bacteria live in a mutually beneficial state with the host. However, the formation of polymicrobial biofilm communities with pathogenic properties may trigger an inadequate host inflammatory‐immune response, leading to the disruption of tissue homoeostasis and development of disease. Because of their unique characteristics, MSCs are suggested as crucial regulators of tissue regeneration even under such harsh environmental conditions. The heterogeneous effects of bacteria on MSCs across studies imply the complexity underlying the interactions between stem cells and bacteria. Hence, a better understanding of stem cell behaviour at sites of inflammation appears to be a key strategy in developing new approaches for in situ tissue regeneration. Here, we review the literature on the effects of oral bacteria on cell proliferation, differentiation capacity and immunomodulation of dental‐derived MSCs.